Analisis Dampak Covid-19 Terhadap Pemasaran Ikan Hias Koi (Cyprinus carpio), (Studi Kasus Di Umkm Niki Koi Garden, Panjer, Denpasar) - I Putu Andre Suryadana; Dewa Nyoman Sadguna; I Gusti Ngurah Sugiana (Fakultas Pertanian, Universitas Warmadewa, 2021)
COVID-19 is an infectious disease caused by the corona virus that has an impact on various sectors including the health, education, tourism and economic sectors. One of the impacts in the economic sector is the Fishery MSME (micro small and medium enterprises) sector. The purpose of this study was to find out the Impact of Covid-19 on the Marketing of Koi Ornamental Fish (Cyprinus carpio) at the Niki Koi Garden MSME (micro small and medium enterprises). This study uses data analysis techniques with qualitative descriptive methods, data collection in this method by collecting data, compiling data and drawing conclusions. Determination of the sample in this study using the method of porposive sampling. The research data were collected by means of observation, interviews, literature study and documentation. The results of this research were obtained: (1) there were differences in the marketing strategy of koi fish before the Covid-19 pandemic and during the Covid-19 pandemic, (2) there were differences in profits obtained before the Covid-19 pandemic and during the Covid-19 pandemic, before the Covid pandemic. -19 from January 2019 – January 2020 earned a profit of IDR 60,660,000 which was obtained from gross income minus expenses (IDR 294,660,000 – IDR 234,000,000). and during the Covid-19 pandemic from March 2020 – March 2021, you will get a profit of IDR 9,470,000 which is obtained from gross income minus expenses (IDR 243,470,000 - IDR 234,000,000. (3) there is no difference in marketing margin before the Covid-19 pandemic 19 and during the Covid-19 pandemic where the marketing margin before the Covid-19 pandemic was IDR 20,000 and during the Covid-19 pandemic the marketing margin was the same as IDR 20,000.